Los conocimientos previos en el aprendizaje del bloque de geometría y medida, de los estudiantes de octavo grado de educación general básica, del colegio de bachillerato Hernán Gallardo Moscoso, de la ciudad de Loja, periodo académico 2018-2019. Lineamientos alternativos. - Tulio Tomas, Castillo Solano (2019)
This research work is about the subject “Previous knowledge in learning the Geometry and Measurement block of eight graders of Basic General Education, of Hernán Gallardo Moscoso High School, of the city of Loja, academic period 2018-2019. Alternative guidelines”, which general objective is to identify how the previous knowledge of eighth graders in basic general education influences in the learning of Geometry and Measurement block; this objective is aimed at demonstrating the hypothesis “Previous knowledge has a significant impact on learning the Geometry and Measurement block of the eight graders of Basic General Education”. The methodology consisted of the application of the methods: scientific, inductive, descriptive, synthetic and hypothetical-deductive, with the help of techniques such as observation, pre-test and post-test, whose instruments consisted of structured questionnaires with 20 questions, applied to a sample of 40 students. The results of the research show that the level of previous knowledge is low, this is evidenced by the average grades obtained after the application of the pre-test and post-test. From the analysis of the data obtained through the instruments applied, it concludes that: Previous knowledge has a significant impact on learning the Geometry and Measurement block; students have little previous knowledge in the Geometry and Measurement block; they also present problems in learning topics such as: lines, angles, triangles, quadrilaterals, polygons of five or more sides, perimeter and area calculation, among others. For this reason it is recommended that at the beginning of the eighth grade of Basic General Education a booster is offered to enhance the knowledge acquired up to seventh grade of Basic General Education.